2022
DOI: 10.1101/2022.06.11.495633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of entomopathogenic fungus Metarhizium robertsii on disease incidence of Faba beans (Vicia faba L.) in field conditions

Abstract: Faba beans (Vicia faba L.) are affected by a large number of pathogens. Studies carried out in western Siberia revealed the influence of the entomopathogenic fungus Metarhizium robertsii on reducing the development and prevalence of a complex of diseases in faba bean in the field. There was a decreasing tendency of the level of phytopathogen infection of seed material and fragments of underground organs during presowing treatment of the bean seeds with M. robertsii. Treatment with M. robertsii significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This work is a part of a comprehensive study of the eff ect of endophytes on the entire agricultural system of the broad bean fi eld, including agricultural plants, fungi and invertebrates, both pests and accompanying species. The characteristics of the colonization of plant tissues and rhizosphere soil by the fungus M. robertsii, as well as the eff ects on plants, are detailed in our previous work [Ashmarina et al, 2022]. We found that soaking broad bean seeds with M. robertsii conidia before planting led to signifi cant decrease in the intensity of plant diseases (root rot, powdery mildew, spotting) even at a relatively low level of plant colonization by the fungus.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…This work is a part of a comprehensive study of the eff ect of endophytes on the entire agricultural system of the broad bean fi eld, including agricultural plants, fungi and invertebrates, both pests and accompanying species. The characteristics of the colonization of plant tissues and rhizosphere soil by the fungus M. robertsii, as well as the eff ects on plants, are detailed in our previous work [Ashmarina et al, 2022]. We found that soaking broad bean seeds with M. robertsii conidia before planting led to signifi cant decrease in the intensity of plant diseases (root rot, powdery mildew, spotting) even at a relatively low level of plant colonization by the fungus.…”
Section: Introductionmentioning
confidence: 71%
“…In June, the colonization of internal tissues of stems and root surfaces reached 18 % and 36 %, respectively, compared to 4 % of Metarhizium-positive plants in the control. In the following months (July-August), the level of colonization decreased to the control values [Ashmarina et al, 2022].…”
Section: S mentioning
confidence: 83%
See 3 more Smart Citations